2012
DOI: 10.1139/w11-113
|View full text |Cite
|
Sign up to set email alerts
|

Does the applicability ofBacillusstrains in probiotics rely upon their taxonomy?

Abstract: The taxonomic position and biological activities of two Bacillus strains used in veterinary probiotics were studied in this work. These microorganisms inhibit growth of a broad spectrum of pathogenic cultures. They synthesize proteolytic enzymes and other biologically active metabolites, and to some extent, supplement each other with probiotic activities. It is not clear whether these versatile activities are properties of individual strains or bacterial taxa as whole. 16S rRNA comparisons were conducted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…(Michna et al, 2015) and DBTBS databases (Sierro et al, 2008). Both species belonged to the same group of related organisms, which were not easily distinguished even by the 16S rRNA sequences (Safronova et al, 2012). We concluded that the transcription regulatory network known for B. subtilis might be fully applied to study the regulation of the orthologous genes in B. atrophaeus.…”
Section: Gene Expression Profilingmentioning
confidence: 94%
See 1 more Smart Citation
“…(Michna et al, 2015) and DBTBS databases (Sierro et al, 2008). Both species belonged to the same group of related organisms, which were not easily distinguished even by the 16S rRNA sequences (Safronova et al, 2012). We concluded that the transcription regulatory network known for B. subtilis might be fully applied to study the regulation of the orthologous genes in B. atrophaeus.…”
Section: Gene Expression Profilingmentioning
confidence: 94%
“…Gene regulation in Bacillus subtilis BSB1 under abiotic stresses was reported by Kohlstedt et al (2014). It was not clear whether these reports could be extended to other PGPR Bacillus, as it had been found that the activities of biotechnological importance were strain specific (Safronova et al, 2012). There was little knowledge regarding plant colonization behavior of other bacteria of the B. subtilis group, such as B. atrophaeus.…”
Section: Introductionmentioning
confidence: 99%
“…Total DNA from cell suspension was isolated using Proba-CTAB (DNA-technology, Russia) DNA isolation kit according to manufacturer' instruction. 16S rRNA gene was amplified with primers 27F and 1492r, sequencing procedures and data analysis was performed as described previously [21].…”
Section: Bacteria Culture Conditionsmentioning
confidence: 99%
“…Незважаючи на те, що бацили описані вже більш як 100 років тому, систематика роду до цього часу розвивається і вдосконалюється. Так, з використанням генетичних методів досліджень було встановлено, що вид Bacillus subtilis складається з групи споріднених видів і підвидів, які можна відокремити один від одного шляхом генетичного типування методом RAPD-аналізу та за сиквенсом гену 16S рРНК [12]. В складі виду B. subtilis виявлено сукупність споріднених видів і підвидів, до яких відносять Bacillus amyloliquefaciens, Bacillus atrophaeus, Bacillus mojavensis, Bacillus vallismortis, Bacil lus velezensis [9].…”
unclassified
“…gov/blast). Філогенетичний аналіз і порівняння нуклеотидних послідовностей гена 16S рРНК представників різних видів роду Bacillus здійснювали як описано у роботі [12]. Дендрограму філогенетичних відносин отримали методом найближчого зв'язування (Neighbor Joining) з ви користанням двухпараметричної моделі Кімури за 100 репліками бутстреп-аналізу з викорис танням програми MEGA 5 [14].…”
unclassified